الاستمالات المستخدمة في الاعلانات التجارية في القنوات الفضائیة الکوردیة و علاقتها بالمضمون الاعلاني - محمد, سلام نصرالدين (Sulaimani Journal for Humanities, 2021)
The study examines the solicitations used in television advertisements on Kurdish satellite channels and its relationship to the advertising content, an analytical study of the solicitations that were used by advertisers and presented them to viewers. Months and the researcher put the industrial month so that every 5 days of each month were chosen. Among the most important goals that the researcher aims to achieve are: A. Knowing the percentage of the most prominent types of advertisements were displayed on Kurdish satellite channels during the study period. B. . Find out the relationship between the grooming used and the advertising content. C. Knowing the homogeneity of the grooming used for the advertising material. Among the most important results that the researcher reached are: 1. Advertisers use recalls for the purpose of attracting viewers and keeping them with the advertisement for a longer period, by using several technical and objective elements. 2. The use of the favors changes with the change of the types of materials, goods, services and ideas, intended to be announced, and each according to the goal of the advertiser, to change the viewers ’attitudes and to express their final decision and use the product advertised. 3. As part of the emotional appeals used, the use of grooming is due to two main reasons, namely, the type of advertising message, and the method used to display the materials intended to be advertised. 4. It was found that there is a good relationship between those grooming that were chosen for the purpose of communicating the advertising idea by the advertiser and the advertising material that was announced about it, as well as the existence of good coordination between the grooming used and the method used.